STRATEGIC PRIORITIES FOR ENSURING THE ECONOMIC SECURITY OF DOMESTIC ENTERPRISES IN THE CONTEXT OF EUROPEAN INTEGRATION - REVENKO, Olena; MINENKO, Sofiia; UVAROV, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
It has been established that, among the external challenges and internal vulnerabilities that particularly affect the modern global economic environment, the main ones are military risks, energy instability, exchange rate fluctuations, disruptions to logistics chains, and a decrease in investment attractiveness. In this context, the priority tasks for domestic enterprises remain the establishment of an effective system of economic security that meets European standards for doing business. It has been proven that in modern business conditions, economic security ceases to be only a matter of protection against traditional threats (raiding, fraud, corruption, etc.), and becomes an essential strategic requirement for ensuring the sustainability and competitiveness of enterprises, and should be reoriented to technological security and innovation, financial stability and transparency, the sustainability of supply chains and institutional security. It is determined that the development and implementation of strategic priorities are critical for domestic enterprises to turn the challenges of European integration into a source of rapid growth, ensure their long-term viability, and become reliable elements of the European economic system. The main strategic priorities that should become basic guidelines when forming the policy of economic security of domestic enterprises are systematized, including innovative development of the enterprise, diversification of sales markets, energy security of the enterprise, financial stability and transparency, digital transformation of management, environmental safety and sustainable development, as well as personnel security and development of human capital. It is substantiated that the set of strategic goals of economic protection forms a system of measures to strengthen the competitiveness of domestic enterprises and orients them towards innovation, openness, responsibility, and adaptation to the requirements of the European market. Such an approach, in our opinion, is the key to sustainable development and integration into the single economic space of the European Union.